Tailings Dewatering And Filtering Using The Metso VPA Filter - H. G. Hedlund (International Mineral Processing Congress, 2012)
Tailings in Mining Industry can be handled in different ways. Today tailings disposal is in focus by projecting new plants as well as treating and handling of old Tailings dams.The trend today is to process minerals, detoxify the Tailings and place them as dry surface Deposition or Underground Backfill. This paper will briefly present five different Mining plants in North and Central America, where Tailings have to be dewatered for dry depositing. The Metso-Sala VPA is a filter especially developed for dewatering and drying of Mineral Concentrate and Mineral Tailings. Keywords: tailings disposal, dewatering, drying, mineral tailings